Intellectual Capital as A Basis of Service Performance on Village Credit Institution - I Gede Riana; I wayan Suana; Kastawan Mandala (Penerbit Kemala Indonesia, 2018)
Entering the ASEAN Economic Community (AEC) has forced various business organizations to change the business paradigm from labor based business or traditional patterns lead to a modern business that is knowledge-based business. This study aims to analysis the role of Intellectual capital (human capital, relational capital and structural capital) in developing the service performance at Village Credit Institutions (VCI). This research was conducted at 35 VCI in the Municipalities over Denpasar, Indonesia. Here, the 35 VCI’s was tested to obtain hypotheses using descriptive and inferential analysis Partial Least Square (PLS). The results of the study concluded that human capital and relational capital are significantly influence on services performance. In contrast, structural capital does not significantly influence on service performance.